Ethnomathematics Study: The Traditional Game of Tikam Bana as a Medium for Learning Mathematics - Siti Rahmawati; Hidayu Sulisti (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to identify the elements and concepts of mathematics contained in the game of tikam bana. In addition, the traditional game of tikam bana must also be introduced so as not to be left behind by the progress of the times, where children have begun to be eroded by some modern technology. The method used was ethnography with the subject of five class VIII students at SMP Pondok Pesantren Assalam Kota Pontianak. The data collection techniques used were observation and documentation. This technique is to obtain information and data about the elements of mathematics contained in the tikam bana game performed by students. Data obtained or collected by researchers from various existing sources. Then the data obtained will be drawn conclusions through the data triangulation process. The results of the research were obtained in the form of questionnaires and assessments carried out while playing by giving test questions on each of the deepest numbers in the plot of tikam bana. The mathematical elements contained in the game of tikam bana are flat, namely square and trapezoid. The concept of mathematics in this game is the concept of integers known at the time of assessment and giving test questions, while the concept of chance is known when doing hompimpa to determine the order of players.